Molecular Characterization of the Myoliquefactive Fish Parasite Kudoa mirabilis (Cnidaria, Kudoidae) from SW Indian Ocean and Its Phylogenetic Relationship with the Kudoa thyrsites Species Complex - Lucilla Giulietti; Egil Karlsbakk; Paolo Cipriani; Salome Daniel Shayo; Julia E. Storesund; Arne Levsen (Microorganisms, 2020)
Myxosporean parasites of the genus Kudoa are fish parasites of great economic importance, as some species can affect the fish fillet quality by producing macroscopic cysts or generating post mortem myoliquefaction, commonly referred to as ‘soft flesh’. Kudoa mirabilis is a ‘soft flesh’-inducing species originally described based on morphology in the musculature of Trichiurus lepturus from the Indian Ocean. An integrative morphological and genetic characterization of K. mirabilis from the type host caught off the coast of Tanzania is here provided. The spores were stellate with four unequal polar capsules, showing similarities to Kudoa thyrsites. For comparative and validation purpose, K. mirabilis was compared morphologically and genetically with K. thyrsites reference isolates, including new obtained samples from the type host Thyrsites atun caught in the SE Atlantic Ocean. Morphological analyses of spores revealed key diagnostic characters clearly distinguishing the two Kudoa species. Phylogenetic analyses based on SSU and LSU rRNA genes demonstrated that K. mirabilis is a distinct and valid species, representing a sister group to a K. thyrsites subclade that comprises several isolates from Japan and one single isolate from South Africa. This finding raises questions about the true diversity likely hidden in the K. thyrsites complex.